2011
DOI: 10.1021/nn200586s
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Nanotextured Microelectrodes Overcome the Molecular Transport Barrier To Achieve Rapid, Direct Bacterial Detection

Abstract: Detection of biomolecules at low abundances is crucial to the rapid diagnosis of disease. Impressive sensitivities, typically measured with small model analytes, have been obtained with a variety of nano- and microscale sensors. A remaining challenge, however, is the rapid detection of large native biomolecules in real biological samples. Here we develop and investigate a sensor system that directly addresses the source of this challenge: the slow diffusion of large biomolecules traveling through solution to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
145
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 121 publications
(147 citation statements)
references
References 33 publications
1
145
0
1
Order By: Relevance
“…Many applications in infectious disease testingincluding testing of swab samples for health-care-associated infections or sexually transmitted infections, or the testing of urine for infectious pathogens-yield samples that contain concentrations higher than 1 cfu ml À 1 . This detection and speed combination also approaches the diffusional limits for large molecules in static solutions 30 .…”
Section: Detection Of Urinary Tract Infection Pathogensmentioning
confidence: 84%
See 1 more Smart Citation
“…Many applications in infectious disease testingincluding testing of swab samples for health-care-associated infections or sexually transmitted infections, or the testing of urine for infectious pathogens-yield samples that contain concentrations higher than 1 cfu ml À 1 . This detection and speed combination also approaches the diffusional limits for large molecules in static solutions 30 .…”
Section: Detection Of Urinary Tract Infection Pathogensmentioning
confidence: 84%
“…By restricting growth within these apertures, we then grew micron-sized tree-like electrodes via electrodeposition, resulting in nanostructured microelectrodes that protrude from the surface and reach into solution. It was previously shown that the micron-sized scale of the protruding electrodes increases the cross-section for interaction with analyte molecules 30 , whereas the nanostructuring maximizes sensitivity by enhancing hybridization efficiency between tethered probe and the analyte in solution 31 . Here these structures are being used to enable the creation of layered, insulated electrode arrays (Fig.…”
mentioning
confidence: 99%
“…It is therefore important to develop a fabrication technique whereby disorder can be produced on large scales and with controllable features. In order to assemble a broadband ENZ nanomaterial, we used an electroplating process that grows a random networks of gold (Au) nanowires from a flat metallic Au substrate [32][33][34][35] (Figure 1). Figure 2a shows SEM cross sections of a fabricated sample.…”
Section: Materials Design and Absorption Resultsmentioning
confidence: 99%
“…31 Nanoelectrode devices offer an attractive option in this field due to their small footprint and potential for high sensitivity. As a result of the versatility and variety of nanoelectrode devices, they have been employed for the detection of a large range of medically relevant analytes ranging from small molecules such as dopamine [32][33][34] and histamine 35 to larger, more complex targets like bacteria 36 or pharmaceutical drugs. 37,38 Enzyme based biosensors have long been of interest because of the selectivity of enzymes as biorecognition elements.…”
Section: Healthmentioning
confidence: 99%